2022
DOI: 10.1002/adsu.202200039
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Rapid Removal of Pb(II) Ions by a Nano‐MoS2 Decorated Graphene Aided by the Unique Combination of Affinity and Electrochemistry

Abstract: co-precipitation, [11] cloud point extraction, [12] flocculation, [13] reverse osmosis, [14] and adsorption, [15,16] the adsorption-based removal methodology is one of the most promising and widely applied methods to remove pollutants from the environment due to its cost-effectiveness, simple operation, and environmental friendliness. [17] However, the efficiency of adsorption in the removal of toxic metal ions such as Pb (II) depends on the selectivity of the materials used toward the particular ions because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…In our previous report, the ultra-rapid and selective adsorption of Pb(II) by prGO-MoS 2 was explained based on the combination of affinity (between Pb(II) and the S 2− and O moieties) and the electrochemistry mechanism (imparted by the electron-rich prGO). 28 There, it was observed that MoS 2 In this study, the presence of oxidation peaks observed in DPV for Pb(II) and Cd(II) on prGO-MoS 2 (Figure 3A) is evident in the EC mechanism, i.e., the spontaneous reduction of Pb(II)/ Cd(II) to Pb(0)/Cd(0), by prGO-MoS 2 . The absence of these peaks in both MoS 2 and pm-prGO+MoS 2 (Figure 3B) indicates the absence of an EC mechanism in these materials.…”
Section: Possible Mechanism For the Simultaneous And Selective Ec Sen...mentioning
confidence: 95%
See 2 more Smart Citations
“…In our previous report, the ultra-rapid and selective adsorption of Pb(II) by prGO-MoS 2 was explained based on the combination of affinity (between Pb(II) and the S 2− and O moieties) and the electrochemistry mechanism (imparted by the electron-rich prGO). 28 There, it was observed that MoS 2 In this study, the presence of oxidation peaks observed in DPV for Pb(II) and Cd(II) on prGO-MoS 2 (Figure 3A) is evident in the EC mechanism, i.e., the spontaneous reduction of Pb(II)/ Cd(II) to Pb(0)/Cd(0), by prGO-MoS 2 . The absence of these peaks in both MoS 2 and pm-prGO+MoS 2 (Figure 3B) indicates the absence of an EC mechanism in these materials.…”
Section: Possible Mechanism For the Simultaneous And Selective Ec Sen...mentioning
confidence: 95%
“…The detailed synthesis procedure of prGO-MoS 2 is reported elsewhere by our group; GO, sodium molybdate, and thioacetamide were used as the precursor, and a simple hydrothermal route was followed. 28 The synthesis procedures followed to obtain prGO-MoS 2 are elaborated in the Supporting Information (Page No. S1).…”
Section: Synthesis Of Prgo-mosmentioning
confidence: 99%
See 1 more Smart Citation
“…During recent years, researchers used MoS 2 and its composites as efficient adsorbents. [72][73][74][75][76] As reported in our previous work, 2 the regions of adsorption isotherms of MnO -4 on MoS 2 and their boundaries under different conditions were analyzed by the ARIAN model and were shown in Table S2. Using data of this Table, the appropriate initial concentrations of MnO -4 were determined for carrying out adsorption kinetic tests.…”
Section: Kinetics Of Adsorption Of Mno -4 On Mosmentioning
confidence: 99%
“…The emergence of 2D materials [1][2][3][4][5][6][7][8] had a tremendous impact on the scientific research, in consideration of the unique properties and their broad technological prospect in photonics, [9] flexible electronics, [10] nanocomposites, [11,12] (photo)electrocatalysis, [13][14][15] supercapacitors, [16,17] functional coatings, [18] (bio)sensors, [19] and desalination. [11,[20][21][22]…”
Section: Introductionmentioning
confidence: 99%